Classroom Interaction Patterns in EFL Task- Based Classroom - Bobi Arisandi (Journal of ELT Research: The Academic Journal of Studies in English Language Teaching and Learning, 2018)
The research was conducted to find out the interaction pattern that emerged when lecturer used Task-Based Instruction in EFL (English as a Foreign Language) classroom at the third semester of English Study Program of Sekolah Tinggi Keguruan and Ilmu Pendidikan Muhammadiyah Kotabumi-Lampung. Researcher used third semester of speaking class students as the participants. The data was taken by using three instruments which were classroom observation, questionnaire and interview. The research was qualitative research. The result of this study revealed a conclusion. There were two kinds of interaction in the classroom during the use of Task-Based Instruction. The interactions that emerged were student-lecturer interaction and student-student interaction. The finding of this research can be beneficial as suggestions in two following area; theoretical and practical. In the theoretical area, this research can be useful for enriching the existing theory of classroom interaction, especially for teaching English as Foreign Language in Indonesia. On practical area, this research can be useful for lecturer to broaden the understanding toward classroom interaction and researcher for further research on classroom interaction.